One threat, two paths: A social identity model of age discrimination's asymmetric impact on older workers' knowledge seeking and sharing. - Zhang, Fangfang; Iles, Lucinda; Andrei, Daniela; Zoszak, Leah; Parker, Sharon K. (Journal of Occupational & Organizational Psychology, 2026)
Organizations risk losing invaluable expertise as the workforce ages, a problem exacerbated when age discrimination discourages older workers from sharing and seeking knowledge. Drawing on the workplace inclusion framework and work design theory, this study investigates a moderated mediation model where perceived age discrimination hinders knowledge transfer by diminishing older workers' sense of belongingness and uniqueness. We further propose that task significance, a core work design feature, buffers these negative effects by making the broader impacts of older workers' efforts more salient and enhancing feelings of social embeddedness and contribution. A three‐wave time‐lagged survey of 296 older Australian workers supported our hypotheses. The results showed that age discrimination indirectly hindered knowledge sharing via diminished belongingness and uniqueness, but hindered knowledge seeking only via belongingness. Importantly, task significance buffered the negative impact of discrimination on both belongingness and uniqueness, thereby mitigating the negative indirect effects on knowledge transfer. These findings contribute to theory by distinguishing the distinct pathways through which age discrimination impairs knowledge transfer and by demonstrating that meaningful work can serve as a critical resource to protect older workers from age‐discriminatory environments.